High-quality surrounding landscapes mitigate avian extirpations from forest remnants - Anderson S. Bueno; Chase D. Mendenhall; Marina Anciães; Luiz dos Anjos; Víctor Arroyo-Rodríguez; Marco Aurélio-Silva; Cristina Banks-Leite; Matthew G. Betts; Arthur A. Bispo; Andrea Larissa Boesing; Marconi Campos-Cerqueira; Olivier Claessens; et al. (Proceedings of the National Academy of Sciences, 2026)
The species–area relationship (SAR) has long been used to predict extirpation rates from habitat loss, but these rates depend not only on habitat area but also on the surrounding landscape and species’ habitat specialization. We collated global data from forest islands created by river damming and forest fragments resulting from clear-cut deforestation to examine the effects of matrix type (aquatic or terrestrial) and tree cover on avian SARs. Unlike oceanic islands, which are often millions of years old, anthropogenic forest islands provide a contemporary analog to forest fragments to understand matrix effects on SARs and serve as a baseline for worst-case scenarios of forest fragmentation. Our database comprises 50 datasets from 45 studies conducted in tropical and subtropical regions, totaling 1,954 bird species detected through 39,197 incidence records from 336 forest islands and 669 forest fragments. We found that bird extirpation rates were lower in fragments than on islands, especially for forest-dependent species compared to all species. Species losses were further reduced by increasing tree cover around forest remnants at local landscape scales of 300 m, highlighting the importance of small-scale conservation strategies. Moreover, even small forest fragments with greater nearby tree cover held high conservation value, emphasizing the crucial role of the surrounding landscape in mitigating avian extirpations from forest remnants. Beyond protecting forest remnants themselves, area-based conservation efforts would therefore be greatly enhanced by improving matrix quality and expanding tree cover in otherwise hostile landscapes.